Building Environmental Awareness Through Podcasts: Its Impact on Elementary School Students' Listening Skills - Eka Puspitasari, Anealish; Subiyantoro, Slamet; Yulisetiani, Septi (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Listening skills are an important part of developing children's knowledge, so it is necessary to choose the right learning media. Podcasts have advantages that are relevant to listening skills and instill environmental awareness in elementary school students. This study aims to explore the influence of using podcast media in building environmental awareness among elementary school students and its impact on their listening skills. The method used in this study is a descriptive qualitative approach, involving fourth grade students from several elementary schools as participants. Data were collected through in-depth interviews, observations, and analysis of podcast content used in learning. The results of the study showed that the use of podcasts as a learning medium was effective in increasing students' environmental awareness. Students involved in podcast listening activities showed a significant increase in listening skills, which was reflected in their ability to understand and discuss environmental issues raised in the podcast. In addition, students also showed a more caring attitude towards the environment, which was marked by active participation in environmental activities at school. This study concluded that podcast media not only functions as a tool to improve listening skills, but also as an effective means to build environmental awareness among elementary school students. These findings are expected to contribute to the development of more innovative and responsive learning methods to environmental issues.